Pulsed radiofrequency of the brachial plexus in the treatment of chemotherapy‐induced peripheral neuropathy of the upper limb. Issue 1 (11th March 2019) - Vinagre, J. M.; Doody, K.; Harmon, D.
Summary: We describe the treatment of chemotherapy‐induced peripheral neuropathy in the upper limb of a patient via ultrasound‐guided pulsed radiofrequency of the brachial plexus. A 54‐year‐old female, who underwent chemotherapy and mastectomy for left‐sided breast cancer, presented to the pain clinic describing continuous and severe shock‐like pain in the posterolateral aspect of the left upper limb, above the elbow. A diagnosis of chemotherapy‐induced peripheral neuropathy was made. Pain management with multi‐modal analgesia was not fully effective and pulsed radiofrequency was offered as an alternative. Ultrasonography of the supraclavicular region was used to identify the brachial plexus, followed by pulsed radiofrequency using an insulated‐tip needle that produced paraesthesia in the affected area. Onset of pain relief occurred one week post‐procedure and lasted approximately 10 weeks. An estimated 80% decrease in pain intensity was reported by the patient. We propose that pulsed radiofrequency can be offered as a pain management alternative in certain presentations of chemotherapy‐induced peripheral neuropathy.